Outside the box : for ages 9-11 - Potter, Molly (London : A & C Black, 2007)
This photocopiable book is full of innovative, user friendly, exciting and unusual activities that promote creative thinking and problem solving skills in upper KS2. The activities in this book are ideal for less intensive teaching times across the school year - at the end of term (particularly after SATs in Year 6), at the beginning of term when a teacher wants to get to know the class or just when a teacher wants to do 'something different' to make pupils think 'outside the box'.
Keywords: Creative thinking in children; Education, Elementary -- Activity programs -- Great Britain; Problem solving in children